Absolute treatment effects of novel oral antidiabetic drugs on cardiovascular mortality and hospitalization for heart failure: a meta-analysis of digitalized individual patient outcomes. (3rd October 2022) - Wolff, G; Lin, Y; Akbulut, C; Brockmeyer, M; Parco, C; Hoss, A; Sokolowski, A; Westenfeld, R; Kelm, M; Roden, M; Schlesinger, S; Kuss, O
Abstract: Background and purpose: Absolute treatment effects of novel oral antidiabetic drugs for cardiovascular outcomes have thus far not been comprehensively evaluated. We thus aimed to perform a meta-analysis of digitalized individual patient data. Methods and results: Individual patient outcomes from Cardiovascular Outcome Trials (CVOTs) evaluating dipeptidyl peptidase-4 (DPP-4) inhibitors, glucagon-like peptide-1 (GLP-1) receptor agonists and sodium glucose transporter 2 (SGLT2) inhibitors against placebo with time-to-event information for cardiovascular mortality (CM) and/or hospitalization for heart failure (HHF) endpoints were digitalized from Kaplan-Meier plots; Weibull regression models with random-effects meta-analysis were used to estimate numbers-needed-to-treat (NNT) and Meta-NNT with 95% confidence intervals (CI). Sixteen CVOTs reported time-to-event information (14 in primary diabetes, two in primary heart failure populations). Thirteen studies including 96, 860 patients were meta-analyzed for CM: at the median follow-up of 30 months, Meta-NNTs were 178 (64 to ∞ to −223) for DPP-4 inhibitors, 261 (158 to 745) for GLP-1 receptor agonists and 118 (68 to 435) for SGLT2 inhibitors. Ten studies including 96, 128 patients were meta-analyzed for HHF: at the median follow-up of 29 months, estimated Meta-NNTs were −644 (229 to ∞ to −134) for DPP-4 inhibitors, 441 (184 to ∞ to −1100) for GLP-1 receptor agonists and 126 (91 to 208) for SGLT2 inhibitors. SGLT2 inhibitors were especially effective for HHF in primary heart failure populations (Meta-NNT 25 (19 to 39)) vs. primary diabetes populations (Meta-NNT 233 (167 to 385)) at 16 months of follow-up. Conclusion: We found modest treatment benefits of GLP-1 receptor agonists and SGLT2 inhibitors for CM and HHF in primary T2DM populations. In primary heart failure populations, however, SGLT2 inhibitor benefits were substantial and comparable to established heart failure medication. Funding Acknowledgement: Type of funding sources: None.